Pengukuran Tingkat Kapabilitas Tatakelola Infrastruktur Jaringan Pemerintah Daerah Provinsi Gorontalo - Nur Sigit Sulistya Hadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The network infrastructure is the foundation for the application of information technology ( IT ) as well as an asset complex due to the rapid technological developments and changing needs of the organization that need to be managed to maximize performance ¬ right in supporting the achievement of organizational goals . Network infra ¬ structure that was built by the Local Government (LG ) Gorontalo province until 2013 have linked 51 points consisting of 32 agencies , 10 Regional Technical Services Unit dots , 3 dots in the district / city and a 6 point hotspots in public places. This study measured the levels of governance capability of Gorontalo Province Government network infrastructure using the framework kerja Control Objective for Information and Related Technology 5 ( COBIT 5 ) . IT - Related Goals are used , namely the optimization of IT assets , resources and capabilities sertakeamanan information, processing infrastructure and aplikasi.Pengukuran using 16 processes in COBIT 5 and 8 respondents who are managing the network infrastructure that is obtained by mapping 16 process used with responsibility employees.